PENERAPAN MEDIA KUIS INTERAKTIF EASY TEST MAKER PADA SISWA KELAS XI SMA NEGERI 7 KUPANG - Benufinit, Yonly Adrianus; Enstein, Jhon; Patola, Fitry Hestriyani (FKIP Universitas Citra Bangsa, 2024)
Abstract. The lack of use of online-based learning media during learning activities is something that needs to be considered in today's technological developments. Teachers need to optimize various online learning media in order to facilitate and attract students' attention in learning in class and at home. The application of interactive quiz media is one of the steps in introducing students to online learning media. This research is intended to determine students' understanding in the application of interactive quiz media. The purpose of this study was to determine how the process of applying online-based interactive quiz media and to see students' responses to the results of using online-based quiz media in informatics subject learning activities in class XI SMA Negeri 7 Kupang. This research belongs to the type of ex-post facto research (Kerlinger, 1993). In this study, research instruments are needed which include the application of online-based interactive quiz media related to the level of satisfaction and the results of student questionnaires, then the data obtained are processed by inferential analysis. The data collection technique was carried out by means of a questionnaire. In this study, the independent variable (X) is the application of online-based interactive quiz media in learning informatics subjects. For the dependent variable (Y) in this study is student satisfaction when learning using online-based interactive quiz media. The results of the study obtained from the questionnaire calculation of the process of applying online-based interactive quiz media obtained 89% of students at the Sangat Setuju level. Then the results of the calculation of student questionnaires about the satisfaction of online learning on average learning outcomes of 92%. This means that all students are said to be satisfied and successful in using online-based interactive quiz media when learning informatics subjects. Abstrak. Minimnya penggunaan media pembelajaran berbasis online saat kegiatan pembelajaran menjadi hal yang perlu diperhatikan dalam perkembangan teknologi sekarang ini. Guru perlu mengoptimalkan berbagai media pembelajaran online agar dapat memudahkan dan menarik perhatian siswa dalam belajar di kelas maupun di rumah. Penerapan media kuis interaktif merupakan merupakan salah satu langkah dalam mengenalkan kepada siswa tentang media pembelajaran online. Penelitian ini dimaksudkan untuk mengetahui pemahaman siswa dalam penerapan media kuis interaktif. Tujuan dari penelitian ini untuk mengetahui bagaimana proses penerapan media kuis interaktif berbasis online dan melihat tanggapan siswa terhadap hasil penggunaan media kuis berbasis online pada kegiatan pembelajaran mata pelajaran informatika di kelas XI SMA Negeri 7 Kupang. Penelitian ini termasuk ke dalam jenis penelitian ex-post facto (Kerlinger, 1993). Dalam penelitian ini diperlukan instrumen penelitian yang meliputi penerapan media kuis interaktif berbasis online berkaitan dengan tingkat kepuasan dan hasil angket siswa, kemudian data yang diperoleh diolah dengan analisis inferensial. Teknik pengumpulan data dilakukan dengan cara kuesioner. Dalam penelitian ini variabel bebas (X) adalah penerapan media kuis interaktif berbasis online dalam pembelajaran mata Pelajaran informatika. Untuk variabel terikat (Y) dalam penelitian ini yaitu kepuasan siswa saat pembelajaran menggunakan media kuis interaktif berbasis online. Hasil penelitian didapatkan dari perhitungan angket proses penerapan media kuis interaktif berbasis online diperoleh 89% siswa pada tingkat Sangat Setuju. Kemudian hasil perhitungan angket siswa tentang kepuasan pembelajaran online rata-rata hasil belajar sebesar 92%. Berarti semua siswa dikatakan puas dan berhasil dalam penggunaan media kuis interaktif berbasis online saat pembelajaran mata pelajaran informatika.